The Role of Corporate Governance, Earnings Management, and Financial Transparency on Investor Trust - Eko Cahyo Mayndarto; Setia Permana; Ira Kurniati; Aziz Septiatin (Malaqbi Publisher, 2026)
This study examines the role of corporate governance, earnings management, and financial transparency in influencing investor trust among publicly listed companies. In increasingly competitive and information-sensitive capital markets, investor trust represents a critical determinant of market stability and firm valuation. Using a quantitative explanatory research design and panel data analysis of firms listed on the Indonesia Stock Exchange during the 2020–2024 period, this study investigates the direct effects of governance mechanisms, discretionary accrual practices, and disclosure transparency on investor confidence. The results indicate that corporate governance has a positive and significant effect on investor trust, suggesting that effective oversight and accountability mechanisms enhance financial reporting credibility. Financial transparency demonstrates the strongest positive influence, confirming that clear, comprehensive, and timely disclosures substantially reduce information asymmetry and strengthen investor confidence. Conversely, earnings management is found to negatively and significantly affect investor trust, indicating that manipulative reporting practices undermine perceived reliability and increase investment risk. The model explains a substantial proportion of the variance in investor trust, emphasizing the importance of governance quality and reporting integrity in capital market performance. These findings highlight that firms seeking to sustain long-term investor confidence must strengthen governance structures, minimize opportunistic earnings manipulation, and enhance transparency in financial reporting practices.